Characterization and functional analysis of hsp21.8b: An orthologous small heat shock protein gene in Tribolium castaneum. (6th May 2018) - Xie, J.; Xiong, W.; Hu, X.; Gu, S.; Zhang, S.; Gao, S.; Song, X.; Bi, J.; Li, B.
Abstract: Small heat shock proteins (sHSPs) act as molecular chaperones and are widely distributed in all kinds of organisms. Comparative analysis revealed that an orthologous shsp was present during insect evolution. Here, hsp21.8b, one insect orthologous shsp, had been identified in Tribolium castaneum . Quantitative real‐time PCR illustrated that Tchsp21.8b was expressed in all developmental stages, along with the lowest expression at early embryonic stage and relative high expression at other stages especially in late eggs and late pupae. In the adult period, Tchsp21.8b exhibited the highest expression level in central nervous system and followed in elytron, epidermis, ovary and fat body. Moreover, it was upregulated 3.39‐fold in response to enhanced heat stress (45°C) for 4 hr but not to cold stress (4°C) and was upregulated by 1.73‐ to 1.94‐fold under ultraviolet (UV) exposure during 4–6 hr. It was also downregulated by 20.8%–41.8% under starvation in 3 days and had a "down‐up‐down" trend under the pathogen stresses. Larval RNA interference of Tchsp21.8b caused 40.6% insects mortality and reduced the oviposition amount by 66.0% and only 21.0% of the ds‐ Tchsp21.8b eggs could hatch into larvae. These results suggested that as an orthologous shsp, Tchsp21.8b not only plays important roles in the growth, development and fecundity of T. castaneum but with the competence to resist the environment stresses, although the response is relatively weak compared to other hsps . Results from this study also uncovered the functions of the orthologous shsp in the development and anti‐stresses ability of T. castanuem . It provided more scientific evidence for revealing the physiological mechanisms of shsps of the insects and enhanced the capabilities to control different pests.